Risk Analysis of Family Businesses and Non-Family Businesses in Pekanbaru: Comparative Study Before and During Covid-19 - Al Hafizh, Muhammad; Noor, Nor Raihana Asmar Mohd (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2024)
This study aims to analyze business risks between family businesses and non-family businesses in Pekanbaru City, focusing on statistical comparisons before and during the COVID-19 pandemic. The pandemic has changed business significantly, affecting the family and non-family business sectors differently. This research uses a qualitative descriptive research approach with the data collection techniques used in this research interviews and documentation. The data is then analyzed statistically to compare business risks, including business performance indicators, finances and other factors that influence the two types of business. Comparative statistical analysis was used to identify significant differences in business risk between the two groups over the two time periods.